Analysis of the Use of Electronic Medical Records on the Effectiveness of Outpatient Services at the Siulak Mukai Health Center in 2024: Analisis Penggunaan Rekam Medis Elektronik terhadap Efektivitas Pelayanan Rawat Jalan di Puskesmas Siulak Mukai Tahun 2024 - Mandasari, Cica Puspita (Procedia of Engineering and Life Science, 2025)
To improve the quality of health services, health workers are needed who have competencies in accordance with their education and training. Competent health workers are able to provide appropriate services and one of the outpatient health services provided by the government is the Siulak Mukai Health Center. In an effort to modernize and increase the efficiency of the health service system, the government provides a medical record supporting information system, namely the Electronic Medical Record (RME). Siulak Mukai Community Health Center has implemented an electronic medical record system (RME) as an effort to improve the quality and quality of its services. However, there are still some polyclinics that do not fill in complete electronic data due to several obstacles such as network problems at the end of the service and busy nurses and doctors on certain days, as well as the lack of responsibility of health workers in filling in data. on RME. This study aims to determine the impact of using electronic medical records on the effectiveness of outpatient services at the Siulak Mukai Community Health Center. This type of research is quantitative descriptive research. The data analysis method uses quantitative descriptive statistical analysis with the help of SPSS. The research results show that the use of RME has a positive impact on the effectiveness of outpatient services in terms of the aspects of function, program, provisions, objectives and systems at the Siulak Mukai Community Health Center.